Change in cardiometabolic risk factors among Asian Indian adults recruited in a mHealth-based diabetes prevention trial. (September 2021) - Muralidharan, Shruti; Ranjani, Harish; Anjana, Ranjit Mohan; Gupta, Yashdeep; Ambekar, Samita; Koppikar, Varsha; Jagannathan, N; Jena, Sidhant; Tandon, Nikhil; Allender, Steven; Mohan, Viswanathan
Objective: India is experiencing an increasing prevalence of type 2 diabetes and cardiovascular diseases. Mobile health technology may be a strategy to reduce the risk of cardiometabolic disorders. This paper reports on the effect of a mobile health intervention on cardiometabolic risk factors. Methods: The mobile health and diabetes intervention was a 12-week reality television-based mobile health program application delivered via videos, short message service and infographics through a smartphone application followed-up weekly by health coach calls. mobile health and diabetes was conducted in a randomized control trial mode randomized controlled trial methodology in three Indian cities (Chennai, Bengaluru and New Delhi) with participants recruited via community screening events. This paper looks at the pre–post changes in cardiometabolic risks among the participants and the place of demography in influencing these. Results: The mobile health and diabetes intervention group experienced a small reduction in waist circumference (1.8 cm) compared to the control group (0.5 cm, p < 0.05) and a greater decrease in systolic blood pressure (2.7 mmHg) compared to the control group ( p < 0.05). The improvements in cardiometabolic risk factors were more pronounced in individuals with obesity, although overall effects were very modest Conclusions: Cardiometabolic risk factors can be reduced with a mobile health application using human coaching, especially in obese individuals, but the improvements are small. To be more effective and clinically meaningful, intensive engagement with the participants is probably required.